Effects of Dyadic Interventions on Quality of Life among Cancer Patients: An Integrative Review - Abha Sharma; Chongjit Saneha; Warunee Phligbua (Elsevier, 2021)
Interventions delivered to cancer patients along with their caregiver as a unit of care indicates dyadic intervention. With the shift of care to home, dyadic interventions are being popular among cancer care. This review aims to identify the dyadic interventions targeting quality of life (QOL) of cancer patient. The current review examined different dyadic interventions for cancer patients from January 2009 to January 2020. PubMed, Psych-info, and CINAHL databases were searched, and 27 studies were included in the review. There were different dyadic interventions for cancer patients including skill based, psychosocial (psycho-educational, educational, counseling), yoga, mindfulness, coping, dance, writing, training along with education, and counseling. Interventions were different in mode of delivery, duration, and delivery personnel. Interventions had improved some aspects of QOL among cancer patients as well as caregivers. Although some aspects of QOL were improved, precise dose and use of different approaches together could be integrated to develop further interventions. Further intervention based on strong theoretical framework guided by the standard protocol is recommended.